The anti-adherence effect of Lippia sidoides Cham: extract against microorganisms of dental biofilm Efeito anti-aderente de Lippia sidoides: extrato contra microorganismos do biofilme dental - A.C.L. Albuquerque; M.S.V. Pereira; D.F. Silva; L.F. Pereira; F.A.C. Viana; J.S. Higino; M.R.V. Barbosa (Universidade Estadual Paulista, 2013)
Most illnesses affecting the oral cavity are proven to have infectious origin. Several categories of chemical agents have been used in the chemical control of dental biofilm through strategies that aim at reducing bacterial adhesion and inhibiting the growth and the proliferation of microorganisms on the tooth surface. The use of plants in folk medicine and in Dentistry, as well as the spread of successful cases, has led to scientific exploration, resulting in chemical-pharmacological knowledge of thousands of plants. The present study aimed to evaluate the anti-adherence activity of Lippia sidoides Cham., comparing the results with those of 0.12% chlorhexidine by means of an in vitro simulation of dental biofilm. The studied bacterial strains were Streptococcus mutans, Streptococcus sanguinis and Lactobacillus casei, main responsible for the biofilm adherence. The studied extract was effective in inhibiting the adherence of Streptococcus mutans up to a concentration of 1:16, compared to Chlorhexidine. Lippia sidoides Cham extract showed anti-adherence effect on the major microorganisms responsible for dental biofilm consolidation. É fato comprovado que a maior parte das doenças que acometem a cavidade bucal são de origem infecciosa. Várias categorias de agentes químicos têm sido utilizadas no controle químico do biofilme dental através de estratégias que visam a redução da adesão bacteriana, a inibição do crescimento, e a proliferação dos microrganismos na superfície do dente. A utilização das plantas pela medicina popular, seu uso na Odontologia e a divulgação dos êxitos, conduziram a exploração científica resultando no conhecimento químico-farmacológico de milhares de plantas. A presente pesquisa objetivou avaliar a atividade antiaderente da folha da Lippia sidoides Cham. comparando seus resultados com a Clorexidina 0,12%, através de uma simulação, in vitro, do biofilme dental. As linhagens bacterianas utilizadas na pesquisa foram o Streptococcus mutans, Streptococcus sanguinis, e o Lactobacillus casaram, principais responsáveis pela aderência do biofilme. O extrato estudado mostrou-se efetivo na inibição de aderência das bactérias ensaiadas até uma concentração de 1:16, sobre o Streptococcus mutans, sendo comparável à Clorexidina. O extrato da Lippia sidoides Cham. demonstrou efeito antiederente, sobre os principais microrganismos responsáveis pela consolidação do biofilme dental.